Contours of Positivity as Determinants of Maternal Psychological Well-Being in Pakistani Children with and without Hearing Impairment. Issue 4 (4th July 2022) - Masood, Afsheen; Sulman, Muhammad; Kamran, Fatima; Ashraf, Farzana; Arshad, Arooj
ABSTRACT: The current research was designed in order to investigate the differences in hope, gratitude and psychological well-being in mothers of children with and without hearing impairment. This is hypothesised that there is likely to be significant differences in hope, gratitude and psychological well-being in mothers of children with and without hearing impairment. The sample for the current research comprised of n = 300 ( n = 150 mothers of children with hearing impairment who were compared with mothers of hearing children ( n = 150, after matching them on core subject variables); children within age ranges of 12–18 years were selected through non-probability purposive sampling. The scales included Hope Trait Scale, Psychological Well-Being Scale and Gratitude Questionnaire. Independent Sample t -test revealed significant differences in hope, gratitude and psychological well-being in mothers of children with and without hearing impairment. Pearson Product Moment correlation revealed significant positive relationship among hope, gratitude and psychological well-being in mothers of children. Regression analyses revealed that hope and gratitude are significant predictors of psychological well-being. The findings are promising for counsellors, teachers and mothers to change the perception and views regarding disability to seek better results in their children's functioning.